Total Laparoscopic Hysterectomy with Prior Uterine Artery Ligation at Its Origin - Poojari, Vidyashree Ganesh; Bhat, Vidya Vishwanath; Bhat, Ravishankar (International Journal of Reproductive Medicine, 2014)
We compared the duration of surgery, blood loss, and complications between patients in whom both uterine arteries were ligated at the beginning of total laparoscopic hysterectomy (TLH) and patients in whom ligation was done after cornual pedicle. Using a prospective study in a gynecologic laparoscopic center, a total of 52 women who underwent TLH from June 2013 to January 2014 were assigned into two groups. In group A, uterine arteries were ligated after the cornual pedicles as done conventionally. In group B, TLH was done by ligating both uterine arteries at the beginning of the procedure. All the other pedicles were desiccated using harmonic scalpel or bipolar diathermy. Uterus with cervix was removed vaginally or by morcellation. The indication for TLH was predominantly dysfunctional uterine bleeding and myomas in both groups. In group A, the average duration of surgery was 71 minutes, when compared to 60 minutes in group B (P<0.001). In group A, the total blood loss was 70 mL, when compared to 43#x2009;mL in group B (P value < 0.001). There were no major complications in both groups. To conclude, prior uterine artery ligation at its origin during TLH reduces the blood loss and surgical duration as well as the complications during surgery.